Clinical profile of patients with acute ischemic stroke receiving intravenous thrombolysis (rtPA-alteplase) - Prasad Jagini, Shiva; I., Suresh (International Journal of Advances in Medicine, 2018)
Background: Stroke patients are at highest risk death in the first few weeks after the event, and between 20-50% die within first month depending on type, severity, age, co-morbidities and effectiveness of treatment of complications. Objective of this study was to clinical profile of patients with acute ischemic stroke receiving intravenous thrombolysis (rtPA-alteplase). Methods: Prospective Observational study of 26 cases of acute ischemic stroke receiving IV thrombolysis using rtPA-alteplase at Kovai Medical Centre Hospital, Coimbatore over a period of 1 year 9 months. Results: 21 cases had NIHSS score of range 10 to 22. The mean NIHSS score at admission is 13.5. 15 subjects (57.7%) had achieved primary outcome in this study. MRS Score of 0 to 2 is considered as favorable outcome. In this study 20 subjects (76.92 %) had favorable outcome at the end of 3 months. Conclusions: Majority of the patients receiving rtPA-alteplase had favorable outcome.